Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T10:11:44+01:00
(x-a)²+(y-b)²=r²

(a,b) <--środek okręgu
r- promień

x²+y²-6x+2y-6=0 /+6
x²-6x+y²+2y=6

korzystamy z wzoru skróconego mnożenia
(x-a)²=x²-2ax+a²
zatem:
x²-6x=x²-2ax więc a=3
ale:
(x-3)²=x²-6x+9 więc o 9 za dużo (musimy je odjąć obustronnie)
(x-3)²-9=x²-6x

korzystamy z wzoru skróconego mnożenia
(y-b)²=y²-2by+b²
zatem:
y²+2y=y²-2by więc b=-1
ale:
(y-(-1))²=(y+1)²=y²+2y+1
(y+1)²=y²+2y+1 odejmujemy 1
(y+1)²-1=y²+2y

PODSTAWIAMY
[x²-6x]+[y²+2y]=6
(x-3)²-9+(y+1)²-1=6
(x-3)²+(y+1)²-10=6 /+10
(x-3)²+(y+1)²=16

środek O=(3,-1)
r²=16, więc r=4